2012
DOI: 10.3340/jkns.2012.52.5.435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bone Cement Volume and Stiffness on Occurrences of Adjacent Vertebral Fractures after Vertebroplasty

Abstract: ObjectiveThe purpose of this study is to find the optimal stiffness and volume of bone cement and their biomechanical effects on the adjacent vertebrae to determine a better strategy for conducting vertebroplasty.MethodsA three-dimensional finite-element model of a functional spinal unit was developed using computed tomography scans of a normal motion segment, comprising the T11, T12 and L1 vertebrae. Volumes of bone cement, with appropriate mechanical properties, were inserted into the trabecular core of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…In this study, we suggested as high as a 27.8% infusion ratio as an effective ratio for favorable outcomes. The ratio was similar to that of Kim et al14), whose in vitro study determined that a 30% infusion ratio was effective for strength and stiffness recovery. In our study, the mean infusion ratio of the favorable group was 25.21±7.14% in the first week follow up.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this study, we suggested as high as a 27.8% infusion ratio as an effective ratio for favorable outcomes. The ratio was similar to that of Kim et al14), whose in vitro study determined that a 30% infusion ratio was effective for strength and stiffness recovery. In our study, the mean infusion ratio of the favorable group was 25.21±7.14% in the first week follow up.…”
Section: Discussionsupporting
confidence: 79%
“…There are multiple studies, which investigated the correlation between the intravertebral cement volume and the clinical outcome through in vitro , in vivo and experimental studies 912131416171824). However, the consensus has not yet been established, since the optimal cut-off value varies according to each study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a treatment for Kummell disease, PKP may immediately alleviate pain and restore the stiffness and strength of the vertebral body through the stability and support provided by PMMA (20). Kim et al (21) reported that a bone cement volume of 30% of the vertebral body volume restored the level of stiffness to that of normal bone. However, if the bone cement volume exceeded 30% of the vertebral body volume, the stiffness exceeded that of normal bone.…”
Section: Discussionmentioning
confidence: 99%
“…[132][133][134] An important component of any polymer to be used in drug delivery, is that the polymer must be biocompatible. Moreover, biocompatible polymers used for drug delivery are often biodegradable and have byproducts, which are nonharmful, such as non-toxic alcohols, acids, and other relatively easily eliminated products.…”
Section: A Polymers In Drug Deliverymentioning
confidence: 99%